2016
DOI: 10.1152/ajplung.00226.2015
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical WNT-5B signaling induces inflammatory responses in human lung fibroblasts

Abstract: COPD is a progressive chronic lung disease characterized by pulmonary inflammation. Several recent studies indicate aberrant expression of WNT ligands and Frizzled receptors in the disease. For example, WNT-5A/B ligand expression was recently found to be increased in lung fibroblasts of COPD patients. However, possible effects of WNT-5A and WNT-5B on inflammation have not been investigated yet. In this study, we assessed the regulation of inflammatory cytokine release in response to WNT-5A/B signaling in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Such an upregulated Wnt5B and remodeling-related gene expression were also observed in the air-liquid interface- (ALI-) cultured PBEC cell model, particularly in the cells from COPD patients [50]. In line with this finding, van Dijk et al recently demonstrated that Wnt5B induced inflammatory responses in human lung fibroblasts [53]. In this study, the authors ascertained inflammatory cytokine releases of human lung fibroblasts, and their results showed that Wnt5B had an ability to induce CXCL8 release in MRC-5 human fibroblasts upon Wnt5A/B simulation.…”
Section: Molecular Mechanisms Of Wnt Signaling In Pathogenesis Of mentioning
confidence: 76%
See 2 more Smart Citations
“…Such an upregulated Wnt5B and remodeling-related gene expression were also observed in the air-liquid interface- (ALI-) cultured PBEC cell model, particularly in the cells from COPD patients [50]. In line with this finding, van Dijk et al recently demonstrated that Wnt5B induced inflammatory responses in human lung fibroblasts [53]. In this study, the authors ascertained inflammatory cytokine releases of human lung fibroblasts, and their results showed that Wnt5B had an ability to induce CXCL8 release in MRC-5 human fibroblasts upon Wnt5A/B simulation.…”
Section: Molecular Mechanisms Of Wnt Signaling In Pathogenesis Of mentioning
confidence: 76%
“…Importantly, canonical Wnt signaling activity was decreased in experimental emphysema mouse models, and an activation of Wnt/ β -catenin activation using lithium chloride (LiCl) led to an attenuation of experimental emphysema, as ascertained by an elevated expression of alveolar epithelial cell markers, decreased airspace enlargement, reduced collagen contents, and improved lung function [14]. Apart from Wnt/ β -catenin signaling, noncanonical Wnt5A/B and their receptor FZD8 were upregulated or activated by TGF- β 1 in pulmonary fibroblasts and lung tissues or CS from COPD patients, which impaired endogenous lung repair and induced inflammatory responses in COPD lung [46, 50, 53]. …”
Section: Implications Of Wnt Signaling In Copd and Ifpmentioning
confidence: 99%
See 1 more Smart Citation
“…CS-E was shown to act as a co-receptor for Wnt and a direct receptor for the receptor for advanced glycation end-products (RAGE) 26 . Since the activation of human lung fibroblasts including HLF cells is mediated by RAGE 27 and Wnt, 28 it is thought that CS-E activates fibroblasts at least through RAGE and/or Frizzled pathways. Interestingly, lung fibroblasts themselves express CHST15, a specific producer of CS-E. Blockade of CHST15 reduced collagen synthesis by fibroblasts, suggesting that CHST15 provides signals to synthesize collagen as well as CS-E in lung fibroblasts (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this approach was results from other tissues, such as skeletal muscle, heart muscle and skin, in which WNT signalling has been described to be involved in tissue fibrosis [16-18]. There also seems to be an association of WNT signalling with transforming growth factor beta signalling [15], and in lung fibroblasts WNT5B was directly able to induce inflammatory processes [19]. Data from our own group has also shown TGF beta and WNT signalling to be altered in scar tissue from patients with vesico-urethral anastomotic stricture (VUAS) after radical prostatectomy (RP) [20].…”
Section: Introductionmentioning
confidence: 99%